(untitled) (Malaysian Journal of Learning and Instruction, 2023)
Purpose - Innovation is imperative to address a wide array of challenges in higher education. The term “microclass” is coined by the researcher to describe the division of a large class into smaller classes, which are handled by student facilitators who have undergone microteaching and performed similar teacher tasks to facilitate students, assessment, discussion, and feedback. Methodology - This was an explorative study and employed the triangulation method (self-designed questionnaire, observation by teacher peers, and semi-structured interview) as well as thematic and descriptive analysis to evaluate the roles of the teacher and student facilitators, level of engagement, and effectiveness of this innovation in the teaching-learning process for the subject, biology. Findings - Data revealed that the role of the teacher and student facilitators concurred to work responsibly in a synergistic manner as implementers of microclass. The teacher, conducted microteaching, observed, supervised, consulted, and provided feedback to the student facilitators. The student facilitators acted as discussant, motivator, collaborator, coordinator, and executor of initiatives such as scaffolding and pair method throughout the duration and stages of the microclass, resulting in an organized classroom. Furthermore, the microclass was innovatively effective and improved student engagement in the teaching-learning process, which in turn developed soft skills among the students—leadership, commitment and discipline. Significance - It assists science teachers in constructively engaging their students in learning science including boosting students’ soft skills, essential for 21st-century skills education and thus warrants further investigation.